Top ten challenges when interfacing a laboratory information system to an electronic health record: Experience at a large academic medical center. (October 2017) - Petrides, Athena K.; Tanasijevic, Milenko J.; Goonan, Ellen M.; Landman, Adam B.; Kantartjis, Michalis; Bates, David W.; Melanson, Stacy E.F.
Highlights: Description of operational, clinical, laboratory and technical challenges experienced when implementing an interfaced EHR-LIS. Tips and suggestions on how to successfully manage system design, implementation and stabilization of an interfaced EHR-LIS. Important metrics to utilize to identify issues and measure improvements associated with an interfaced EHR-LIS. Resource management and training guidelines for providers and laboratory staff prior to and during an EHR-LIS implementation. Abstract: Background: Recent U.S. government regulations incentivize implementation of an electronic health record (EHR) with computerized order entry and structured results display. Many institutions have also chosen to interface their EHR to their laboratory information system (LIS). Reported long-term benefits include increased efficiency and improved quality and safety. In order to successfully implement an interfaced EHR-LIS, institutions must plan years in advance and anticipate the impact of an integrated system. It can be challenging to fully understand the technical, workflow and resource aspects and adequately prepare for a potentially protracted system implementation and the subsequent stabilization. Objectives: We describe the top ten challenges that we encountered in our clinical laboratories following the implementation of an interfaced EHR-LIS and offer suggestions on how to overcome these challenges. Methods: This study was performed at a 777-bed, tertiary care center which recently implemented an interfaced EHR-LIS. Challenges were recorded during EHR-LIS implementation and stabilization and the authors describe the top ten. Results: Our top ten challenges were selection and harmonization of test codes, detailed training for providers on test ordering, communication with EHR provider champions during the build process, fluid orders and collections, supporting specialized workflows, sufficient reports and metrics, increased volume of inpatient venipunctures, adequate resources during stabilization, unanticipated changes to laboratory workflow and ordering specimens for anatomic pathology. A few suggestions to overcome these challenges include regular meetings with clinical champions, advanced considerations of reports and metrics that will be needed, adequate training of laboratory staff on new workflows in the EHR and defining all tests including anatomic pathology in the LIS. Conclusion: EHR-LIS implementations have many challenges requiring institutions to adapt and develop new infrastructures. This article should be helpful to other institutions facing or undergoing a similar endeavor.